Aplikasi edible coating pati sagu meranti ekstrak lengkuas merah sebagai antioksidasi pada apel Malang kupas - Vonny Setiaries Johan; Dewi Fortuna Ayu; Hijratun Amini (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Red galangal is a type of rhizome that is known to have many benefits. This study aims to get the best concentration of red galangal extract in an edible coating of meranti sago starch as an antioxidant in peeled Malang apples. The research was conducted as an experimental method, using different concentrations of red galangal extract, which are 0%, 1%, 3%, 5%, and 7% in the edible coating formulation, which was applied to peeled Malang apples and stored for eight days at 5°C. The parameter observed in the edible coating was antioxidant activity. The parameters observed in peeled Malang apples were browning index, vitamin C, weight loss, total dissolved solids, and the descriptive and hedonic sensory test of taste and flavor. Data were analyzed statistically using ANOVA and continued with DNMRT at a 5% level. Edible coating with 7% red galangal extract was the best treatment, with an IC50 of 158.41 µg/ml showing moderate antioxidant activity. On the 8th day of storing, the peeled apples had a 936.05 browning index, 3.64 mg/100g vitamin C, 45.40% weight loss, and 1.40°brix total dissolved solids. The peeled apple's sensory descriptively assessment results on taste and flavor were typical of galangal and apples. The sensory hedonistic assessment results of the peeled apples on taste and flavor were similar.